Hubungan Pengetahuan Dengan Sikap Suami Tentang Aktifitas Seksual Pada Istri Menopause di Desa Bandar Kuala Kecamatan Galang Kabupaten Deli Serdang Tahun 2024 - Pardede, Desikawali; Turnip, Meria; S, Susilawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Menopause is the final phase in a woman's life cycle, where menstrual bleeding stops completely. At around 50 years of age, women enter menopause which is marked by a decrease or loss of the hormone estrogen, which often causes complaints or disorders that can interfere with daily activities. The design of this study is a descriptive correlation with a cross-sectional approach. The study was conducted in Bandar Kuala Village, Galang District, Deli Serdang Regency, during the period October 2018 to March 2024. The population of this study consisted of 40 people, with a sample of 36 people. Data analysis was carried out univariately and bivariately using the product moment test with a significance level of 95% (α = 0.05). The results of the study regarding knowledge showed that the majority of respondents, namely 19 people (52.8%), had sufficient knowledge. Meanwhile, regarding attitudes, the majority of respondents, namely 20 people (55.6%), showed negative attitudes. Based on the results of the relationship between knowledge and attitudes of husbands about sexuality of menopausal wives in Bandar Kuala Village, Galang District, Deli Serdang Regency, the p value was obtained = 0.0047 (p ≤ 0.0047). This shows that there is a significant relationship between knowledge and attitudes of husbands about sexuality of menopausal wives in the village